Assessment of Human Factors Causes of Occupational Risk in the Chemical Industry Using the Analytic Network Process (ANP) Method - Patradhiani, Rurry Patradhiani; Maimana (International Journal of Science, Technology & Management, 2021)
The development of the industry in Indonesia is inseparable from the analysis of the production process and identification of the risk of causing work accidents. In every production process in the chemical industry there are various risks that cause occupational accidents, the biggest cause of accidents comes from human factors. It required a priority assessment of workplace accidents influence on the human factor as the cause of the rising incidence of labor in the production process in the chemical industry with the method of Analytic Network Process (ANP) , of the assessment results using ANP method can be determined to set a risk management strategy causes of accidents. ANP method is done by determining goals, criteria, and sub criteria. In this case the criteria are the production process and the sub criteria are human factors that cause the risk of work accidents. Furthermore, the value of influence between criteria is determined, between criteria and sub criteria and between sub-criteria . The results obtained are the highest limiting values for criteria, namely the final product process and sub-criteria, namely human factors not using PPE . Strategies that can be taken to control risk is by giving reward and punishment, providing HSE training, as well as the management is partially responsible for HSE